KEPIMPINAN WANITA DALAM POLITIK DARI PERSPEKTIF SIYASAH SYAR’IYYAH - Syed Ismail, Sharifah Hayaati (Jurnal Syariah, 2019)
This article tries to elaborate the position of women leaders in Islam according to various opinions given by the fuqaha ’. Besides, the writer also gives suggestions on which opinion is preferable and recommendable according to the situation in Malaysia vis-a-vis the political and administrative system as well as the capability of Muslim women in the country.